Sustainable development of concrete through treated and untreated plastic waste aggregates - Ekkachai Yooprasertchai; Ahsan Khursheed; Muhammad Irshad Qureshi; Ali Ejaz; Qudeer Hussain; Amorntep Jirasakjamroonsri; Panumas Saingam (Scientific Reports, 2024)
This study focused on sustainable and novel development of concrete through treated and untreated plastic waste aggregates. In this study, the surface of Elec-waste coarse aggregates was treated with sulfuric acid, marble dust coating, silica fume coating, and alkaline bleach. Elec-waste aggregates were used in concrete by replacing natural coarse aggregates in amounts of 10%, 20%, and 30%. The 10%, 20%, and 30% Elec-waste replacement ratios resulted in the compressive strength reduction of 8.97%, 27.99%, and 42.01%, respectively. The same percentage of Elec-waste aggregates reduced the splitting tensile strength by 21.77%, 35.89%, and 47.89%, respectively. However, the slump was observed to increase by 41.4%, 52.1%, and 68.8%, respectively. All the considered treatments enhanced the performance of Elec-waste aggregate concrete (E-WAC). Overall, the best improvement in the performance of E-WAC was imparted by silica fume coating, irrespective of the quantity of Elec-waste aggregates. The present study proposed an expression to estimate the reduction of the compressive strength of E-WAC. It was demonstrated that the equation by JCI-08 predicted splitting tensile strength of E-WAC close to experimental results.
Keywords: Recycled Aggregate Concrete Performance; Innovative concrete reinforcement materials; Innovations in Concrete and Construction Materials